Governance as a Determining Factor of Corporate Social Responsibility Disclosure in Sharia Banking - Pratama, Siectio Dicko (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2022)
This research analyses the influence of Good Corporate Governance and Corporate Social Responsibility (CSR) expenditure on Corporate Social Responsibility (CSR) disclosure at Islamic Banks in Indonesia (BI), which has already been registered in Bank Indonesia (BI) since 2014- 2018. The collection methods used in this research is the data sourced in an annual report published by the website of each Islamic Bank. The collection of samples used is the purposive sampling technique. The total sample of this research is 12 Islamic Banks listed by Bank Indonesia since 2014-2018. The result showed that Investment Account Holder (IAH) and Government Ownership significant to Corporate Social Responsibility (CSR) disclosure. On the other hand, governance of the Sharia Supervisory Board (IG-SCORE), institutional ownership, foreign ownership, and CSR expenditure have no significant CSR disclosure